Visualisasi `Si Pitung` Berdasarkan Cerita Margreet Van Till untuk Memotivasi Perjuangan Bela Negara bagi Generasi Muda - Pamungkas, Wisnu Bayu; Arizal, Fariza Wahyu (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2024)
Folklore always exists in every region, including Indonesia. Folklore is a form of culture and/or history of a place to date. Therefore, existing folklore needs to be maintained by creating the latest literacy that adapts to current era and technology. One of them is by making adaptations of folk tales through digital comics based on internet sites, aka web comic. The aim is to make folklore relevant and easily accessible and become better known to the public. This research uses a qualitative method by referring to book that explaining the setting of the era when folklore occurred and relevant literature studies. Supporting media used as promotional material in this research include social media posting, posters, banners, tote bags, key chains, pins, mugs, hand-held fan.